3PC-028 Compounding an oral liquid formulation of diazepam alcohol free. (24th March 2020) - Barbosa, R; Capela, A; Sampaio, C; Fraga, S; Soares, T; Campos, J; Ferreira, D; Costa, P; Bighinati, L
Abstract : Background and importance: Drug shortages is a common international problem. Pharmaceutical compounding is a viable alternative, especially relevant in paediatrics. An example of such a situation is the oral liquid formulation of diazepam, indicated for epilepsy and seizures. However, only formulations that use ethanol as a cosolvent are described in the scientific bibliographies. This excipient is not recommended in paediatrics, with children's age dependent proposed limits by EMA/FDA/WHO. Aim and objectives: To develop an oral liquid formulation of diazepam that is ethanol free. Material and methods: A compounding vehicle, B9, National Compounding Formulary, formulated with the suspending agent Avicel RC581 polymer was used to prepare an oral suspension of diazepam 0.4 mg/mL. Tablets and bulk material were used as drug sources. The stability of the drug was verified over 90 days under different temperature and storage conditions (ambient and refrigerated) with the inhouse high performance liquid chromatography (HPLC) method using the UltiMate 3000 HPLC (Thermo Fisher Scientific, USA). Particle size was measured using the Mastersizer 300 (Malvern Panalytical, UK). Results: After 7 days, more than 10% of drug loss was observed for the ambient storage preparations, both tablets and bulk, and for the refrigerated bulk preparation. The tablet refrigerated formulation maintained >90% of the drug content until the 60 day mark. No significative changes were observed in particle size after 60 days in all samples. The organoleptic characteristics (smell, taste and texture) remained unchanged in all of the preparations until the third month. Conclusion and relevance: A stable alcohol free diazepam suspension was achieved. The tablets produced a more stable formulation than the bulk source, especially when stored at a lower temperature. This formulation can solve the problem of shortages, allowing the appropriate administration of paediatric treatments, while allowing compliance with the recommended composition limits of ethanol, by excluding this excipient from its composition. References and/or acknowledgements: No conflict of interest.